2021
DOI: 10.1037/scp0000237
|View full text |Cite
|
Sign up to set email alerts
|

Domains related to four single/relationship options among sexual minorities raised conservatively religious.

Abstract: Sexual minorities raised conservatively religious often make relationship decisions in a context of conflicting needs and expectations. We examined group differences in a sample of 452 sexual minorities who were equally satisfied in 1 of 4 single/relationship options to promote self-determination and to understand how each group might differ from the others. Single and celibate individuals more often reported homonegative beliefs, religiousness, sex negativity, and conservative values. Single but not celibate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Clients who experience sexual identity confusion and/or conflict are likely to experience competing demands and expectations from a variety of sources, so it is important to make clear to clients that the therapist’s only stake in their clients’ process is their clients’ self-understanding and mental health. Various outcomes have been reported by individuals resolving sexual identity confusion and/or conflict, including pursuing same-gender partnerships, pursuing other-gender partnerships, and refraining from dating or partnering (Lefevor, Beckstead, et al, 2019; Lefevor, Schow, et al, 2021). Being “on the client’s team” involves being primarily committed to helping clients understand the competing demands they experience without a preconceived notion of the best ways to resolve those demands.…”
Section: Principles For Ethical and Effective Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Clients who experience sexual identity confusion and/or conflict are likely to experience competing demands and expectations from a variety of sources, so it is important to make clear to clients that the therapist’s only stake in their clients’ process is their clients’ self-understanding and mental health. Various outcomes have been reported by individuals resolving sexual identity confusion and/or conflict, including pursuing same-gender partnerships, pursuing other-gender partnerships, and refraining from dating or partnering (Lefevor, Beckstead, et al, 2019; Lefevor, Schow, et al, 2021). Being “on the client’s team” involves being primarily committed to helping clients understand the competing demands they experience without a preconceived notion of the best ways to resolve those demands.…”
Section: Principles For Ethical and Effective Therapymentioning
confidence: 99%
“…Similarly, sexual minorities who are content in being single and celibate typically report a lower sex drive than others (Lefevor, Schow, et al, 2021). Many sexual minorities ultimately find happiness and satisfaction in same-gender sexual relationships, although doing so may entail navigating internal and external stigma (Lefevor, Schow, et al, 2021). By exploring clients’ sexual orientation with them and discussing research about different options for relationships or remaining single (e.g., Lefevor, Beckstead, et al, 2019), therapists may empower clients to make informed life choices.…”
Section: Effective Assessment and Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the conservative nature of the faith—in addition to the ways in which the CJCLDS affects culture, community, and overall life—opportunities for the integration of identities are thought to be rare, and few seek out a new faith tradition (Glass et al, 2015). Alternatively, it may be that relationship status (e.g., single and celibate, single and not celibate, mixed orientation relationship, same-gender relationship) is more useful in distinguishing SMs from conservative religious traditions than integration per se (Lefevor, Beckstead, et al, 2019; Lefevor, Schow, et al, 2021). Finally, a review of existing literature suggested that religious SMs might instead be grouped in four different ways: individuals who seek to change their environment (e.g., disaffiliating from nonaffirming religions, seeking out new religions), those who incorporate new beliefs (e.g., using scripture to justify sexual orientation), those who change their behavior (e.g., attempting to cease sexual behaviors with the same sex), and those who compartmentalize (Anderton et al, 2011).…”
Section: Identity Integrationmentioning
confidence: 99%
“…In a fascinating look at how sexual minorities raised in conventionally religious families and communities make relationship decisions, Lefevor et al (2021) report on the experiences of single and celibate gay persons, single but not celibate gay persons, gay persons in mixed orientation marriages in which their spouse is straight, and gay individuals who are in same-sex relationships. As can be seen in this wide array of relationship trajectories, emphasis in their work has been on understanding self-determination in life decisions, which is an important consideration for therapists working with sexual minorities from various religious faith backgrounds.…”
mentioning
confidence: 99%